A solução elegante de Lacan: uma formalização do "Além do Princípio do Prazer" - Henri Kaufmanner (2006)
We took as a starting point in our work, Jacques Lacan.s writing On a Question Prior to Any Possible Treatment of Psychosis. Our investigation was centered on the study of the mathematical elements found on Scheme R and Scheme I, considered by Lacan as topologies referred to how reality is constituted in neurosis and psychosis, respectively. In both schemes it was possible to find some graphics references to the notion of infinity,since they both have asymptotes in their constitution. As we followed on, searching for the origin of those schemes, we found Scheme L, presented by Lacan on Seminary 2. This scheme works, in our point of view, as an organizer of Lacan.s thought during the fifties, and it brings us two main ideas. First, there is a disjunction between the symbolic and the imaginary, and second, there is an insurmountable hiatus between them. According to Lacan, that topology is based on Freud.s Beyond the pleasure principle and it was possible for us to verify that the impossible of the death drive is what keeps the hiatus in its place. We followed the steps Lacan took to show us the disjunction between symbolic and imaginary, beginning with his discussion on Plato.s Menon and we emphasized the importance of maintaining this disjunction. At this moment, in Lacan.s teaching the symbolic is taken as a continuous phrase. The maintenance of the hiatus is fundamental because it avoids the reduction of subject to this continuous symbolic phrase. The imaginary plays an important role there. It crosses the symbolic, and this crossing conciliates the hiatus with the structure of the psychism. Through the use of some apologues and clinical reports we could show, in our work, what kinds of effects on the subject are produced surpassing this hiatus. A completed symbolic or an imaginary totality leads the subject .dangerously. to a death experience. This is what we can see, for example, in Oedipus tragedy, in Freud.s dream known as Irma.s Injection Dream, in Schreber, or in the Cotard Syndrome. We followed studying what kinds of artifices are usually used by the subject to keep the disjunction. It is possible in neurosis, because there is the phallus, significant used by Lacan in a mathematical way when he compares it to the medium and extreme ratio of the harmonic division. The phallus is able to work as a stabilizer element in the relationship between symbolic and imaginary. So, just like the Golden Section ratio, the , the phallus, as a ratio, presents us an irrational side which could allow an articulation with the symbolic and another side that could lead the subject to search the beauty of the form. We also showed that, in psychosis, is exactly the forclusion of this ratio that opens the way for collapsing this disjunction, bringing a large number of symptoms related to the idea of Mental Automatism. The psychotic needs to find another ratio to keep the field of his reality stable. We could demonstrate how Schreber worked on it, and how the solution he found also made possible to articulate the irrational dimension of the symbolic with the imaginary efforts to make One. The elements we could find in the neurosis even in the psychosis stabilization allowed us to find the simplicity of Lacan.s articulation at these times. We called it Lacan.s Elegant Solution.